Parenting attitude and self-concept of fathers having adolescent - Rahman, Md Sohanur; Dastider, Sathi (Journal of Preventive and Social Medicine, 2024)
Background: Parents play a unique role in child-rearing. Though the mother plays a vital role, no one can replace a father's contribution to rearing a child. The purpose of this study was to see whether fathers' self-concept was associated with their parental attitudes. Methods: This was a cross-sectional study conducted during the period from January to December 2021. A total of 188 fathers having at least one adolescent were selected from selected rural areas of the Jashore district in Bangladesh. Data were collected by face-to-face interviews with a semi-structured questionnaire and using convenient sampling technique. The behavioral qualities of the fathers were measured using a variety of scales, including the attitude toward parenthood scale, Campbell's self-concept clarity scale. Statistical Package for Social Science (SPSS) was used to analyze the data in accordance with the study's objectives. Before data collection, informed consent was taken, and ethical concerns were addressed at different stages of the study. Results: The findings revealed that the mean age of the fathers was 44.55±8.515 years and the highest frequency (59.6%) was in the age group 30-45 years. The study finding showed that 94.1% were Muslim and the main occupation of 41.5% of them was agriculture. Among the fathers, a large number had no formal education (33%), 38.8% completed their primary education. The mean working duration was 8.56±1.868 hours. The attitude towards parenthood scale had an average score of 6.45±0.512, mean self-concept score was 46.13±6.169. Fathers' parenting attitude were unaffected by their socio-demographic characteristics such as occupation (p = 0.329), monthly income (r = 0.046, p = 0.534), or expenditure (r = 0.033, p = 0.655), working duration (r = -0.117, p = 0.110). Fathers’ selfconcept was an important variable that showed a significant correlation with fathers' parenting attitude (r = 0.158, p = 0.031). The participating fathers' parenting attitudes did not exhibit substantial mean disparities between their educational status (p = 0.055) and their wives' educational status (p = 0.202). Conclusion: This study revealed that father with better self-concept had enhanced their adolescent care by involving in active parenting. JOPSOM 2023; 42(1):21-28